Nisekoi : false love. Vol. 23, One day - Komi, Naoshi, 1986- (Shonen Jump manga., 2017)
Love triangle! Comedic antics!! Gang warfare?! You won't want to miss out on Shonen Jump 's laugh-out-loud feel-good manga series! It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. On Marika's wedding day, Raku bursts in just before the couple seals their vows. Will Raku and the gang manage to rescue Marika from her mother's minions? And when they return to their ordinary lives, how will the whole adventure affect Kosaki and Chitoge's feelings for Raku?